Sequence of the Pseudomonas aeruginosa trpI activator gene and relatedness of trpI to other procaryotic regulatory genes. - Chang, M (1989)
In Pseudomonas aeruginosa, the trpI gene product regulates the expression of the trpBA gene pair encoding tryptophan synthase. trpI and trpBA are transcribed divergently. The trpI DNA sequence and deduced amino acid sequence were determined. The trpI start codon was found to be 103 base pairs from that of trpB. trpI encodes a 293-residue protein and the size of the trpI gene product, measured on sodium dodecyl sulfatepolyacrylamide gels, was close to that calculated from the amino acid sequence. The amino acid sequence of trpI resembles that of Enterobacter cloacae ampR, the regulatory gene for the ampC cephalosporinase. The N-terminal portions of trpI and ampR resemble corresponding portions of ilvY, metR, and lysR in Escherichia coli and nodD in Rhizobium meliloti. This resemblance may help to define a trpI-related family of activator proteins sharing a common structural plan.